Influence of organisational culture on the implementation of health sector reforms in low and middle income countries : a qualitative interpretive review - Mbau, Rahab Waithira (Health Policy and Systems Division, 2016)
The qualitative interpretive synthesis carried out for this MPH mini-dissertation reviews existing empirical literature for evidence on organisational culture and its influence on the implementation of health sector reforms in Low and Middle Income Countries. This mini-dissertation is organised into three parts: PART A: This is the review protocol which outlines the introduction, the background and the review questions for both the scoping review (which forms section B) and the qualitative interpretive synthesis ( which forms section C) along with their justifications. It also outlines the methodology for both the scoping review and the qualitative interpretive review. The literature search was carried out in eight electronic databases using key search terms developed from the review questions. Inclusion and exclusion criteria were developed to determine the articles for inclusion into the review. All the search terms, data extraction templates and summary tables used in both reviews are provided in this section. PART B: This is the literature review section which was carried out to map the scope of literature on organisational culture within the health sector in Low and Middle Income Countries in order to support the more detailed analysis in Section C. It begins with a general description of organisational culture and its conceptual frameworks, as well as a description of the tools used in assessing organisational culture that were identified from a broader reading of literature on organisational culture. The reviewer then describes the literature search strategy of the scoping review and maps the retrieved articles based on themes on organisational culture in the health sector. Lastly, the reviewer classifies the different dimensions of organisational culture identified in the reviewed articles using the Competing Values Framework in order to facilitate comparison of organisational culture across the studies. PART C: This is the full qualitative interpretive synthesis presented as a journal ready manuscript. This review begins with an introduction on health sector reforms and organisational culture. This is followed by a description of the methods used to identify the literature, an outline and synthesis of the findings, discussion section and lastly, the conclusion. The findings of this interpretive synthesis indicate the potential influence of various dimensions of organisational culture such as power distance, uncertainty avoidance, in-group and institutional collectivism, mediated through organisational practices, over the implementation of the health sector reforms. It also highlights the dearth of empirical literature around organisational culture and therefore, its results can only be tentative. There is need for health policy makers and health system researchers in Low and Middle Income Countries to conduct further analysis of organisational culture and change within the health system.